2012
DOI: 10.1111/j.1600-0579.2012.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

First reflections: third‐year dentistry students' introduction to reflective practice

Abstract: Issues around the assessment of reflective writing are discussed, and students' suggestions for improving their reflective abilities are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…The literature suggests that integrating guided reflective practices into educational programs (through intellectual discourse, journaling, and other methods) enhances course curricula and stimulates self-examination (Jonas-Dwyer, Abbott, & Boyd, 2013; Smith & Trede, 2013). Jakubowski (2003) found that reflection can encourage critical thinking when employed to review social experiences and one’s own reactions to those experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that integrating guided reflective practices into educational programs (through intellectual discourse, journaling, and other methods) enhances course curricula and stimulates self-examination (Jonas-Dwyer, Abbott, & Boyd, 2013; Smith & Trede, 2013). Jakubowski (2003) found that reflection can encourage critical thinking when employed to review social experiences and one’s own reactions to those experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Guidance and supervision are key to assisting reflection and are factors which students find to be beneficial to their learning . Reflective class discussions have also been shown to contribute to students’ reflective learning alongside training seminars aimed at introducing students to the concept of reflection, differing frameworks and levels of reflection and guidelines for writing reflectively . This process of reflection, especially when confronted with unsettling feelings of confusion, doubt and frustration, is central in the lead up to crossing a threshold—”change begins with disruption” 23:.181 and without facilitated reflection to assist in this process it is easy to imagine students becoming disenfranchised, resorting to surface learning techniques or avoidance altogether of the topic, creating a cascade of learning difficulties.…”
Section: Integrating Reflective Practice Tasksmentioning
confidence: 99%
“…Work-based learning provides students with real-life work where they can apply academic and technical skills and develop their employability. [23]…”
Section: Introductionmentioning
confidence: 99%